An Act Incorporating the Cities of Hartford, New Haven, New London, Norwich and Middletown, 1836 Conn. Acts 105 (Reg. Sess.), chap. 1, § 20 - (:unkn) unknown (General Publisher, 1836)
Authorizing the local court of common counsel to prohibit and regulate the storage of gun powder.
--
Keywords: GUN POWDER STORAGE